The diversity of moth fauna (lepidoptera: heterocera) according to altitudes of Taman Negara Johor, Gunung Ledang - Rabihah Ismail,; Azman Sulaiman, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
A total of 1113 individuals of moths representing 167 species in 118 genera under 17 families have been recorded for Johore National Park, Gunung Ledang, based on five sampling occasions conducted on 28 May – 2 June 2014 (P1), 25 – 30 June 2014 (P2), 20 – 25 July 2014 (P3), 17 – 22 August 2014 (P4) and 17 – 22 September 2014 (P5). Samplings had been done at three locations based on different altitudes i.e. location L1 (1100 m), L2 (700 m) and L3 (310 m). The main objective of this research is to provide a preliminary inventory and faunistic aspect of moth in Gunung Ledang. At every sampling location L1, L2 and L3, passive sampling was conducted using light traps of 160 watt mercury vapour light. Samplings were conducted at 1900 to 2300 hours during a dark moon phase. The Margalef’s Species Richness Index (R’) according to the sampling month shows the highest species richness was in P5 (R’ = 12.55) and the lowest at P2 (R’ = 8.28). The R’ value based on altitude shows that the highest was at L1 (R’ = 15.67) and the lowest was at L2 (R’ = 11.50). Analysis of the Shannon Diversity Index (H’) and Evenness Index (E’) based on sampling month shows that the highest H’ was at P5 (H’ = 3.73) and the lowest at P2 (H’ = 3.02) The highest value of E’ was recorded at P5 (E’ = 0.67) and the lowest at P2 (E’ = 0.41).The highest H’ value following altitude was at L1 (H’ = 3.67) and the lowest was at L2 (H’ = 3.47), whereas the highest E’ value was recorded at L3 (E’ = 0.54) and the lowest at L1 (E’ = 0.38). As a whole, the plotted species accumulation curve plotted shows that the curve does not reach the asymptote meaning that further sampling must be done to reach the asymptote. Lyssa zampa (Butler) appeared as the most common species spatially (found in every altitudes) and temporally (found in 12 out of 15 subsamplings). The most abundance species in Gunung Ledang was Pogonopygia nigralbata Warren with total of 131 individuals recorded, whereas the totals of 78 species have been identified as rare species. The highest percentage of overlapping species following sampling month is between P3 and P4 (75%), whereas following altitude is between L2 and L3 (100%).